2004
DOI: 10.1111/j.1460-2695.2004.00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of damage development and failure in notched‐bar multiaxial creep tests

Abstract: Finite element predictions of creep rupture in notched specimens are presented in this work. A damage mechanics model linked to the creep strain rate and stress triaxiality has been adopted in order to predict creep life under multiaxial stress conditions and the predicted creep failure strain and time to rupture have been compared with experimental data for a C-Mn steel tested at 360 o C. Finite element analyses have been conducted for primary-secondary (PS) and primary-secondary-tertiary (PST) creep laws. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 26 publications
(53 reference statements)
1
26
0
Order By: Relevance
“…In previous work [12], [13], FE results of the type shown in Figure 7 have been compared with the NSW model. Here, the predictions from the NSW-MOD model are also considered.…”
Section: Finite Element Prediction Of Creep Crack Growth Ratementioning
confidence: 99%
See 2 more Smart Citations
“…In previous work [12], [13], FE results of the type shown in Figure 7 have been compared with the NSW model. Here, the predictions from the NSW-MOD model are also considered.…”
Section: Finite Element Prediction Of Creep Crack Growth Ratementioning
confidence: 99%
“…A 'virtual' fracture testing procedure using the finite element (FE) method [12][13][14] has been developed to predict creep crack growth rates in Carbon Manganese CT specimens. It has been found that uncoupled continuum damage methods can be used to predict creep crack growth within a numerical framework [14].…”
Section: Finite Element Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) , it no longer has the ability to take the load. Thus it is assumed that the stress components in all directions will be zero in the elements concerned, which is simulated in a similar manner to Yatomi et al (2004) , Oh et al (2011) , Kim et al (2013) and Mehmanparast et al (2014) whereby the material properties of the damaged element (i.e. its stiffness) are reduced to a near-zero value.…”
Section: Modelling Creep Behaviourmentioning
confidence: 99%
“…To predict the onset of crack growth a creep damage approach is used following the approach in [9]. A damage parameter, ω, is defined such that 0 ≤ ω ≤ 1 and failure occurs when ω = 1.…”
Section: Damage Accumulationmentioning
confidence: 99%